SISTEM MONITORING DAN PROTEKSI MOTOR MINI CONVEYOR TERHADAP ANOMALI ARUS DAN TEGANGAN BERBASIS IOT - Kiswantono, Agus (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
The Internet of Things (IoT)-based current monitoring and protection system is an innovative solution for real-time measurement and control of electrical parameters. This study aims to analyze the accuracy of voltage, current, and power readings using the INA19 sensor connected to the Telegram application and compare the measurement results with conventional calculation methods. Testing was conducted by varying the voltage from 150V to 225V using a variac, and the data were compared between smartphone readings, multimeter measurements, and manual calculations. The results indicate that the smartphone-based monitoring system has a high level of accuracy, with a maximum voltage error of 0.93% and a current error of 0.63%. However, at certain test points, the power error percentage fluctuated significantly, reaching 99.22% at 195V. Additionally, the relay-based protection feature effectively detected overcurrent conditions, ensuring device safety by cutting off the electrical current in critical situations. With IoT integration via Telegram, this system enables efficient and real-time remote monitoring without the need for direct conventional measuring instruments. The implementation of this system is expected to improve efficiency and safety in electrical power management in both industrial and residential sectors.